2010
DOI: 10.4067/s0716-078x2010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term research in Bosque Fray Jorge National Park: Twenty years studying the role of biotic and abiotic factors in a Chilean semiarid scrubland

Abstract: Since 1989, we have conducted a large-scale ecological experiment in semiarid thorn scrub of a national park in north-central Chile. Initially, we focused on the role of biotic interactions including predation, interspecific competition, and herbivory in small mammal and plant components of the community. We utilized a reductionist approach with replicated 0.56 ha fenced grids that selectively excluded vertebrate predators and/or larger small mammal herbivores such as the degu, Octodon degus. Although we detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 203 publications
1
62
1
8
Order By: Relevance
“…Temperate agroecosystems follow seasonal abiotic variations that may influence wildlife communities due to the availability of food resources [24,25]. In the Himalayas, Elsen et al [26] demonstrated the importance of low intensity agriculture (small farms with diverse annual crops, orchards and small woodlots) for increasing abundance of forest birds during winter.…”
Section: Introductionmentioning
confidence: 99%
“…Temperate agroecosystems follow seasonal abiotic variations that may influence wildlife communities due to the availability of food resources [24,25]. In the Himalayas, Elsen et al [26] demonstrated the importance of low intensity agriculture (small farms with diverse annual crops, orchards and small woodlots) for increasing abundance of forest birds during winter.…”
Section: Introductionmentioning
confidence: 99%
“…El énfasis que se ha dado a la investigación de largo plazo en cada sitio refleja esta diversidad, como se constata en las tres síntesis de las investigaciones publicadas recientemente (Rozzi et al 2006, Carmona et al 2010, Gutiérrez et al 2010. En su primera etapa de existencia, no obstante la institucionalidad adquirida por la red LTSER-Chile, la diversidad de enfoques ha marcado la aproximación de estudios a largo plazo en cada sitio.…”
Section: Estudios De Largo Plazo En Los Sitios Fundadores De La Red Lunclassified
“…Los resultados de este estudio han permitido detectar el rol clave de la variación interanual en las precipitaciones, lo cual contradice la hipótesis inicial que postulaba a las interacciones bióticas como elementos moduladores en la dinámica de estas comunidades. Es esencial notar que luego de 26 años de estudio, muchas de las hipótesis y percepciones iniciales acerca de la estructura y dinámica de este sistema semiárido de Chile, no solamente cambiaron, sino que requirieron modificaciones en la aproximación experimental y en el monitoreo (Gutiérrez et al 2010). Este experimento ha cambiado a lo largo del tiempo bajo un enfoque de monitoreo adaptativo (Lindenmayer y Likens 2009).…”
Section: Investigación De Largo Plazo En El Parque Nacional Bosque Frunclassified
See 2 more Smart Citations